A facile synthetic route to benzimidazolium salts bearing bulky aromatic N-substituents - Grieco, Gabriele; Blacque, Olivier; Berke, Heinz (Beilstein Journal of Organic Chemistry, 2015)
An atom-economic synthetic route to benzimidazolium salts is presented. The annulated polycyclic systems: 1,3-bis(2,4,6-trimethylphenyl)-1H-benzo[d]imidazol-3-ium chloride (1-Cl), 1,3-bis(2,6-diisopropylphenyl)-1H-benzo[d]imidazol-3-ium chloride (2-Cl), 1,3-diphenyl-1H-benzo[d]imidazol-3-ium chloride (3-Cl), and 1,3-di(pyridin-2-yl)-1H-benzo[d]imidazol-3-ium chloride (4-Cl) were prepared in a two-step synthesis avoiding chromatographic work-up. In the key step triethyl orthoformate is reacted with the corresponding N1,N2-diarylbenzene-1,2-diamines and then further transformed in situ, by alkoxy abstraction using trimethylsilyl chloride (TMSCl), and concomitant imidazole ring closure.
Keywords: benzimidazolium salts; bulky ligands; cyclization; ligand design; N-heterocyclic carbenes (NHC); ring formation